2005
DOI: 10.1002/ana.20697
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 involvement in brain arteriovenous malformations

Abstract: We recently reported that the GG genotype of the interleukin-6 (IL-6)-174G>C promoter polymorphism is associated with clinical presentation of intracranial hemorrhage in brain arteriovenous malformation (AVM) patients. In this study, we investigated whether tissue IL-6 expression was associated with IL-6-174G>C genotype, and whether IL-6 was linked to downstream targets involved in angiogenesis and vascular instability. Our results showed that the highest IL-6 protein levels in brain AVM tissue were associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 37 publications
9
99
0
1
Order By: Relevance
“…We have found that the transduced protein is expressed at 3 days, reaching maximal levels at 3 weeks after viral injection (Fan et al, 2008;Shen et al, 2006a;Zhu et al, 2008). AAV gene transfer did not cause neuronal death and inflammation at 6 days after transduction (Shen et al, 2006b, Shen, 2006. Despite the sustained increase in vascular density, we did not observe any evidence of abnormal vessel morphology for up to 6 weeks following administration of Del-1, using previously published criteria .…”
Section: Del-1 Gene Transfer Induced Cerebral Angiogenesissupporting
confidence: 55%
“…We have found that the transduced protein is expressed at 3 days, reaching maximal levels at 3 weeks after viral injection (Fan et al, 2008;Shen et al, 2006a;Zhu et al, 2008). AAV gene transfer did not cause neuronal death and inflammation at 6 days after transduction (Shen et al, 2006b, Shen, 2006. Despite the sustained increase in vascular density, we did not observe any evidence of abnormal vessel morphology for up to 6 weeks following administration of Del-1, using previously published criteria .…”
Section: Del-1 Gene Transfer Induced Cerebral Angiogenesissupporting
confidence: 55%
“…When IL-6 is expressed in large amounts, there is a significant increase in the mRNA levels of IL-1β, TNF-α, and IL-8 in human AVM tissues. 21 Through the upregulation of these cytokines, IL-6 indirectly stimulates leukocyte recruitment, endothelial activation, and vascular smooth muscle cell (SMC) proliferation (Table 2). Leukocyte recruitment occurs when the cellular adhesion molecules (CAMs) of ECs bind circulating leukocytes and affix them to the site of inflammation.…”
Section: Effect Of Increased Proinflammatory Cytokines On Avms: a Cenmentioning
confidence: 99%
“…Leukocyte recruitment IL-6, TNF-α, and IL-1β 21 Overexpression of E-selectin, ICAM-1, and VCAM-1 22 Angiogenesis IL-6, VEGF, HIF-1, NF-κB, IL-1β, and IL-8 21,59,64 EC proliferation [21][22][23]43 EC migration 22,43 CAM expression 22 Decreased EC apoptosis 43 …”
Section: Inflammatory Mediators Involved Inflammatory Pathwaymentioning
confidence: 99%
“…We found that the GG genotype of the interleukin-6 (IL-6 -174G>C) promoter polymorphism was associated with clinical presentation of ICH [45]. The high risk IL-6 -174 GG genotype was also associated with the highest IL-6 mRNA and protein levels in AVM tissue [13]. We have not yet identified any associations of sporadic AVM with polymorphisms in genes coding for important angiogenesis-related proteins, such as VEGF, TIE-2 or the angiopoietins.…”
Section: Candidate Gene Studies In Avm Patientsmentioning
confidence: 89%
“…MMP-9 expression in particular appears to be orders of magnitude higher in AVM than control tissue [12,27], with levels of naturally occurring MMP inhibitors, TIMP-1 and TIMP-3, also higher, but to a lesser degree. Additional inflammatory markers that are overexpressed include myeloperoxidase (MPO) and IL-6, both of which are highly correlated with MMP-9 [12,13]. MMP-9 expression is correlated with the lipocalin-MMP-9 complex, suggesting neutrophils as a major source.…”
Section: Characterization Of Lesional Tissuementioning
confidence: 99%